The Physical Activity, Sport and Their Impact on Mental Health of Algerian Adolescents (Department of Physical Education, Sport, Health and Recreation, 2016)
This current study examines the effects of physical activity on adolescent’s mental health, in a representative sample both males and females. A total number of 256 adolescents with mean age 16.4 years participated in this study. Mental health was measured by the Mental Health Inventory (MHI-38). A questionnaire was used to estimate physical activity level. This study aims to demonstrate the relationship between PA and mental health, also the type and various levels of physical education and sport in males and females and the various dimensions of mental health. Physical activity is positively associated with mental health for males and female despite the fact that girls score lower in physical activity. Results indicate that the relationship is positive with the wellbeing and negative with distress.The findings suggest that physical activity is associated with adolescents’ mental health, and that beyond primary prevention for distress